1998
DOI: 10.1038/ng0598-60
|View full text |Cite|
|
Sign up to set email alerts
|

Mutations in the human α-tectorin gene cause autosomal dominant non-syndromic hearing impairment

Abstract: The tectorial membrane is an extracellular matrix of the inner ear that contacts the stereocilia bundles of specialized sensory hair cells. Sound induces movement of these hair cells relative to the tectorial membrane, deflects the stereocilia, and leads to fluctuations in hair-cell membrane potential, transducing sound into electrical signals. Alpha-tectorin is one of the major non-collagenous components of the tectorial membrane. Recently, the gene encoding mouse alpha-tectorin (Tecta) was mapped to a region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
220
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 315 publications
(229 citation statements)
references
References 15 publications
3
220
0
2
Order By: Relevance
“…This membrane as an extracellular matrix covers the neuroepithelium of the cochlea and contacts the stereocilia of hair cells transducing sounds into electrical signals. 71 The TECTA gene encodes a precursor protein of 2155 amino acids, determined to contain 23 exons. Mutations in the TECTA gene have Genetic causes of NSHL in Iran N Mahdieh et al been found in both autosomal dominant and autosomal recessive HL (DFNA8/12 and DFNB21).…”
Section: Tecta Genementioning
confidence: 99%
See 2 more Smart Citations
“…This membrane as an extracellular matrix covers the neuroepithelium of the cochlea and contacts the stereocilia of hair cells transducing sounds into electrical signals. 71 The TECTA gene encodes a precursor protein of 2155 amino acids, determined to contain 23 exons. Mutations in the TECTA gene have Genetic causes of NSHL in Iran N Mahdieh et al been found in both autosomal dominant and autosomal recessive HL (DFNA8/12 and DFNB21).…”
Section: Tecta Genementioning
confidence: 99%
“…Mutations in the TECTA gene have Genetic causes of NSHL in Iran N Mahdieh et al been found in both autosomal dominant and autosomal recessive HL (DFNA8/12 and DFNB21). [71][72][73][74] All presented missense mutations lead to the dominant form, whereas inactivating mutations bring about recessive HL. 75 TECTA mutations have been detected in Austrian, Belgian, French and Swedish families.…”
Section: Tecta Genementioning
confidence: 99%
See 1 more Smart Citation
“…Several forms of nonsyndromic deafness or balance defect that result from mutations in genes encoding extracellular proteins have been described in humans and mice. These genes include TECTA (Verhoeven et al, 1998), COL11A2 (McGuirt et al, 1999), COCH (Robertson et al, 1998), and Otog (Simmler et al, 2000). The importance of extracellular matrix proteins in inner ear function, the inner ear-restricted MIAL expression pattern, and the existence of an inactive allele suggest that MIAL may contribute to nonsyndromic hearing impairment or balance defect in humans.…”
Section: Figmentioning
confidence: 99%
“…The linked area on chromosome 11q24 in this family is approximately 20 cM telomeric to FSGS2 locus and has several interesting candidate genes. One such gene, tectorin alpha (TECTA), shares homology with utrophin and is mutated in a dominant form of inherited deafness (33). Utrophin is a paralogue of dystrophin and has two full-length mRNA species, A and B, which have very different expression patterns.…”
Section: Discussionmentioning
confidence: 99%